KONTRIBUSI DISIPLIN KERJA TERHADAP KINERJA GURU MADRASAH ALIYAH NEGERI (MAN) KOTA PADANG PANJANG - Lainah Lainah (IAIN Batusangkar, 2016)
Contribution of Discipline to Teacher Performance of Madrasah Aliyah Negeri (MAN) Padangpanjang. Teachers’ performance was tending to be lower everywhere. It was assumed that this was closely related to their working discipline. This research aimed at revealing the contribution of the teachers’ work discipline and principas instrucstional leadership toward teachers.Performance to do it, this reseach presented three hypotheses: The first, teacher working discipline contributed to teachers’ ferformance; second, contributed to teachers performance, the third, both techers’ working discipline and principals’ instructional leadership contributed simultaneously toward the teacher performance.There were 97 senior high school teachers involved as the population of the research, twenty seven of them were selected as smples by using stratified proportional random sampling technique. Data were collected by using a questionanaire of likert scale model and analyzed by means of correlated and regression techniques. The results showed that: (1) Teachers’ working discipline contributited significantly 47,0% Toward the teachers’ performanc, it can be concluded that the working discipline.Anyway, there must be some other factors contributing which were not discussed in this study. However, the teachers’ working discipline and had been tested to significanty contributed to the teachers’ performance.Kata Kunci: disiplin kerja, kinerja guru